The best American short stories 2023 - Lee, Min Jin; Pitlor, Heidi; Bazile, Cherline; Binyam, Maya, 1993-; Bissell, Tom, 1974-; Bowe, Taryn; Da-Lin; Ehrlich, Benjamin; Freeman, Sara, 1985-; Groff, Lauren; Harris, Nathan; Jackson, Jared; et al. (Best American series., 2023)
A collection of the year's best short stories, selected by National Book Award finalist Min Jin Lee and series editor Heidi Pitlor. Min Jin Lee, author of the highly acclaimed National Book Award Finalist Pachinko, selects twenty stories out of thousands that represent the best examples of the form published the previous year.